All-Quad Meshing for Geographic Data via Templated Boundary Optimization. (2017) - Simons, Lance; Amenta, Nina
Abstract: Motivated by the requirements of groundwater flow simulations in natural resource management, we give an algorithm that produces two-dimensional all-quad meshes of geographic regions with complex boundaries, often defined by rivers, watershed boundaries and geological features. Our algorithm fills the interior of a region with a regular grid, and fills the geometrically complex boundary regions using a global optimization over a choice of templated patches.